The influence of tool rotation speed on the low-cycle fatigue behavior of AA2519-T62 friction stir welded butt joints. (December 2022) - Kosturek, Robert; Torzewski, Janusz; Joska, Zdeněk; Wachowski, Marcin; Śnieżek, Lucjan
Highlights: The effect of tool rotation speed on the stir zone macrostructure and microhardness is discussed. The main places of decohesion in tensile and fatigue testing are reported. For the obtained joints the cyclic stress–strain curves and the Manson-Coffin-Basquin equations are established. Abstract: The subject of this study were the friction stir welded butt joints of the 5 mm thick AA2519-T62 alloy obtained with four various values of tool rotation speed: 200, 400, 600 and 800 rpm, and the constant welding velocity of 100 mm/min. The examination involved macro and microstructure observations, microhardness, tensile, and fatigue testing. An increase in the stir zone size and microhardness has been reported together with increasing tool rotation speed. The weld obtained with the lowest value of tool rotation speed (200 rpm) is characterized by. a significant reduction of microhardness in the SZ, which makes it very susceptible to plastic deformation. In terms of tensile properties, there is a tendency of increasing welds' yield and tensile strength together with increasing applied tool rotation speed. The tensile failures occur in the LHZ, which is located, depending on tool rotation speed, at the SZ (200 rpm), at the HAZ/TMAZ interface (400 rpm) or at the SZ/TMAZ interface (600 and 800 rpm). For AA2519-T62 and its FSW joints, the cyclic strain hardening is stronger than monotonic strain hardening. The LCF behavior of the FSW joints have been described by the parameters of the Manson-Coffin-Basquin, taking into account the Smith-Watson-Topper parameter. The established fatigue parameters indicate that the joints produced with the 400–600 rpm tool rotation speed exhibit the lowest reduction in fatigue strength coefficient. The fractured surfaces have a typical fatigue striation pattern with the participation of secondary cracks and small Al2 Cu particles.